Gelatinases Cleave Dentin Sialoprotein Intracellularly - Gou, Xiaohui; Xue, Yifan; Zheng, Huiwen; Yang, Guobin; Chen, Shuo; Chen, Zhi; Yuan, Guohua (Frontiers in Physiology, 2020)
Dentin sialoprotein (DSP), the NH2-terminal fragment of dentin sialophosphoprotein (DSPP), is essential for dentin formation and further processed into small fragments inside the odontoblasts. Gelatinases, including matrix metalloproteinases 9 (MMP9) and MMP2, were able to cleave DSP(P) in tooth structures. We hypothesized that gelatinases may also cleave DSP intracellularly in the odontoblasts. In this study, the co-expression and physical interaction between DSP and gelatinases were proved by double immunofluorescence and in situ proximity ligation assay (PLA). Intracellular enzymatic activity of gelatinases was verified by gelatin zymography and in situ zymography. To confirm whether DSP was cleaved by active gelatinases intracellularly, lysates of wild-type (WT) odontoblastic cells treated with a MMP2 inhibitor or a MMP9 inhibitor or a MMP general inhibitor and of Mmp9-/- odontoblastic cells were analyzed by western blotting. Compared with the WT odontoblastic cells without inhibitor treatment, all these groups exhibited significantly higher ratios of high molecular weight to low molecular weight band density. FURIN was verified to be co-localized and physically interacted with MMP9 by double immunofluorescence and in situ PLA. The ratio of proMMP9 to activated MMP9 inside the odontoblastic cells were increased when function of endogenous FURIN was inhibited. And overexpressed proMMP9 was intracellularly cleaved by FURIN in the HEK293E cells, which was completely blocked by the mutation of proMMP9 with R96TPR99 substituted by A96AAA99. Taken together, these results indicate that DSP is intracellularly processed by gelatinases, and FURIN is involved in the intracellular activation of proMMP9 through cleavage of its R96TPR99 motif.